Pattern of traffic rules violations and the risk of fatal injuries in Mysuru city - A., Rashmi; B. M., Shrinivasa; B. M., Shrinivasa; B. M., Shrinivasa; M. R., Narayanamurthy; M. R., Narayanamurthy; M. R., Narayanamurthy (International Journal Of Community Medicine And Public Health, 2017)
Background: In India, Road safety is an issue of national concern. Road accidents create negative impact on the economy, public health and the general welfare of the people. Every year the lives of approximately 1.25 million people are cut short as a result of road traffic accidents. Between 20 and 50 million more people suffer non-fatal injuries, with many incurring a disability as a result of their injury. Reliable road traffic injury surveillance is an important component of evidence based road safety policy making. Methods: A cross sectional study was conducted for the period of 3 months in Mysuru city. The present study included all the 5 Traffic Police stations coming under Mysuru city. Before conducting the study, permission to collect all the relevant information is obtained from the in charge of the stations. Retrospective data regarding the traffic rules violations, fatal and non-fatal injuries are obtained in the fixed format prescribed by the government which is maintained uniformly by all the police stations. Data collected was entered in MS office excel sheet and analyzed using statistical package for social sciences (SPSS) software version 22.0. Results: From the study we can observe that there is a drastic increase in the total number of traffic crimes in 2015 compared to 2014. Case fatality of road traffic accident showed decreasing trend from the year 2013. It was evident from the study that there was no significant correlation between total number of accidents every year with violation of traffic rules (r = -0.86 p =0.338). Similarly There was no significant correlation between the number of persons killed every year with violation of rules by riding two wheeler without helmet(r = -0.380 p =0.752). Conclusions: With massive investment in roads and the exponential growth in the number of vehicles it has become necessary to have a system, which integrates all disciplines that influence road safety. In depth evaluation of the road traffic accidents to build infrastructures and to reinforce the regulations specific to local needs is required.